2018
DOI: 10.1159/000492244
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Fibroblast Growth Factor 23 with Arterial Stiffness and Atherosclerosis in Patients with Autosomal Dominant Polycystic Kidney Disease

Abstract: Background/Aims: In patients with autosomal dominant polycystic kidney disease (ADPKD), cardiovascular events are the most frequent cause of mortality and morbidity. The aim of our study is to investigate the association between serum fibroblast growth factor-23 (FGF-23) and arterial stiffness (AS) as determined with brachial-ankle pulse wave velocity (baPWV) and atherosclerosis development as determined with carotid artery intima-media thickness (CA- IMT). Methods: This cross-sectional study was conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(51 reference statements)
0
15
1
Order By: Relevance
“…Furthermore, exposure to FGF23-which is a growth factor-triggers hypertrophy in isolated rat myocardiocytes [122]. Accordingly, high circulating levels of this bone hormone correlate with impaired endothelium-dependent vasodilation [123], increased arterial stiffness [124], and left ventricular hypertrophy [125] in CKD patients. However, the implication of high FGF23 for CV diseases remains unclear.…”
Section: The Endothelium In Ckdmentioning
confidence: 99%
“…Furthermore, exposure to FGF23-which is a growth factor-triggers hypertrophy in isolated rat myocardiocytes [122]. Accordingly, high circulating levels of this bone hormone correlate with impaired endothelium-dependent vasodilation [123], increased arterial stiffness [124], and left ventricular hypertrophy [125] in CKD patients. However, the implication of high FGF23 for CV diseases remains unclear.…”
Section: The Endothelium In Ckdmentioning
confidence: 99%
“…IMT represent an early marker of vascular dysfunction [21]. Several studies have shown higher IMT values in ADPK D than in healthy controls, even before the development of hypertension [22][23][24][25][26]. In our cohort, patients with ADPKD had the lowest IMT, while patients with ADPK D CKD stage 3 presented a similar IMT to controls.…”
Section: Discussionmentioning
confidence: 53%
“…Subsequently, five studies were excluded as two of them did not contain a control group, 29,30 two studies used different procedures for the evaluation of vascular stiffness 31,32 (ie nitroglycerin‐induced dilatation, hand skin heating test) while one article 33 represented a partial duplicate of a study that was already included in the present review. As a result, a total of 27 studies 34‐60 were included, comprising 1967 individuals (1141 ADPKD patients and 826 healthy controls).…”
Section: Resultsmentioning
confidence: 99%